Birokrasi dan Perilaku Budaya Organisasi Di Pesantren - Millah, Nur Ita A’ini Qudwatal; Sari, Nove Kurniati (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2019)
The discussion in this article focuses on the bureaucracy and cultural behavior of the organization in one of the Islamic educational institutions in the city of Yogyakarta. In this paper the author focuses on Al-Munawwir Islamic Boarding School Complex Q Krapyak Yogyakarta in maintaining and advancing its existence towards implementing institutional bureaucracy in building organizational behavior and culture. The research method used was a descriptive qualitative study. Data collection techniques in this paper through observation, interviews, and documentation studies. The results of this study indicate that the success of Islamic educational institutions certainly can not be separated from how the role of a dialogic bureaucracy in the distribution of structures, tasks and institutional elements that are formulated through discussion rooms or deliberations, behavior and organizational culture with a rolling job system and instill attitudes of Islamic moral values and preserving the culture of Javanese people by making it a habit to communicate using local languages to instill cultural values by building a sense of ukhuwah in organizing within the scope of the Al-Munawwir Islamic Boarding School Complex Q Krapyak Yogyakarta